Grouping and genetic diversity of different watermelon ecotypes based on agro-morphological traits and ISSR marker - Soghani, Zeynab Norelahi; Rahimi, Mehdi; Nasab, Maryam Abdoli; Maleki, Mahmood (Iheringia, Série Botânica., 2018)
The genetic diversity of 38 ecotypes of watermelon was evaluated using genetic markers and morphological traits. Analysis of variance showed a signifi cant diff erence for the studied traits. Cluster analysis using UPGMA method based on morphological traits was classifi ed studied ecotypes into four groups. Using 11 primers were obtained 89 polymorphic bands that cluster analysis of molecular data was placed 38 ecotypes into four groups. The genetic diversity structure of the watermelon accessions on the basis of ISSR data evidenced a common pattern of molecular markers. The similarity of ecotypes grouping with molecular markers and morphological traits was low and the correlation coeffi cient of the twomatrices was low (r = 0.03), revealing quite a non-signifi cant correlation between them and the efficiency of them to assays in estimating genetic diversity in watermelon is diff erent. Overall, this study demonstrated high genetic diversity among cultivated watermelon which may be attributed to their high genetic background and environmental effects.